Public policies for training civil workers in Brazil - Luiz Pase, Hemerson; Barcelos, Márcio; Santos, Everton; Dupuy, Ana Paula (Estado, Gobierno y Gestión Pública, 2018)
This paper discusses some epistemological possibilities for the qualification of Brazilian civil servants. To do so, we present two sets of theories, which give importance to institutions, as well as those that value ideas, knowledge and discourses. In light of these theories, we observe the state of the art of the Brazilian public service to solve our main problem, how to train public servants in Brazil? The preliminary results confirm the hypothesis that any training process requires the consideration of several theoretical contributions beyond the complexities of a continental and populous country.